Economics of fodder production for dairying in selected areas of Bangladesh - Islam, S; Begum, J; Sarker, NR; Khatun, M (Bangladesh Journal of Animal Science, 2017)
Dairy farming along with fodder production is a highly profitable enterprise. Considering these views, the studywas aimed to estimate profitability of fodder production, to determine the income coefficient of fodder farm householdsand to assess the contribution and impact of fodder production on livelihood change. In this regard, six study areas were selected from six districts viz: Dinajpur, Jessore, Kurigram, Rangpur, Pabna and Sirajgonj considering the concentration of fodder production and dairy farming systems. A purposive sampling technique was followed for collecting primary data from the field. Two categories of sample farmers were selected namely: i) Fodder Producer cum Seller; ii) Fodder Producer cum Dairy owner having 1-2 dairy cows as small, 3-4 dairy cows as medium and 5 and above dairy cows as large farmer. A total of 220 fodder farmers were interviewed. Field survey method and focus group discussions were followed to collect necessary data and information. Descriptive statistics and Cobb Douglas type revenue function were applied to get the meaningful results. The production cost of fodder for producer was estimated Tk. 1,82,415/ha and for producer cum seller Tk.1,79,748/ha. On average, total cost was estimated Tk. 1,81,081/ha/year irrespective of fodder producer. Bio-mass yield was found 207ton/ha/year and per ton fodder price was estimated Tk.1,714. On the contrary, annual net return from fodder production was estimated Tk.1,67,823/ha/year and Tk.1,81,489/ha/year for producer and producer cum seller, respectively. The BCR was 1.92 for producer and 2.01 for producer cum seller. Functional analysis revealed that fodder sale and livestock rearing and fodder business significantly contributed to the household income of the fodder farmers. The dairy farmers having 1-2, 3-4 and 4-5 cross-bred dairy cattle earned Tk. 1,20,227, Tk. 1,91,728 and Tk. 4,17,287, respectively, whereas local cattle earned Tk. 33, 658, Tk. 51,601 and Tk. 1,13,558, respectively from milk sell annually. For addressing the impact on livelihood status of the dairy farmers with fodder production, it was found improved human capital component over time acquiring knowledge and education, better health condition, easy and more entrance to information, etc. Cultivable land, using open water resources and forests were indicated to determine the changes situation in the natural capital aspects. In case of financial capital, cash in hand, savings and liquid assets had increased notably over the periods. Physical assets had also observed positive trends in the study regions. Thus, dairy owner cum fodder farmers overall livelihood status had shown a positive trend. Bang. J. Anim. Sci. 2017. 46 (2): 140-149